The impact of COVID-19, lockdowns, and vaccines on the Philippine stock market - Sañga, Michael Harvey J.; Sañga, Michael Harvey J.; Mendoza, Adrian R. (Quezon City School of Economics, University of the Philippines Diliman, 2022)
This paper examines the effect of the COVID-19 pandemic on stock returns and stock volatility of firms listed in the Philippine Stock Exchange (PSE). We apply fixed effects panel data regression to analyze the impacts of the growth rates of COVID-19 cases and deaths as well as the different levels of lockdowns on stock returns. As an extended analysis, we incorporate the growth rate of COVID-19 vaccine doses administered as a control for pharmaceutical intervention. We also estimate the impacts of COVID-19 on stock returns at the sectoral level. The study covered the period January 30, 2020 to September 15, 2021. The results show that the growth rates of COVID-19 cases and deaths have negative effects on stock returns, while the lockdowns in general positively impact stock returns when not controlling for vaccine administration. The results also show that the growth rates of COVID-19 confirmed cases and deaths increase stock volatility and that stricter lockdowns decrease volatility in the presence of effective pharmaceutical interventions.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: COVID-19 Pandemic, 2020-2023 -- Economic aspects